(untitled) (Minerva. Revista de Filología Clásica, 2019)
The language of Satyr-Drama occupies an intermediate stage between the language of Tragedy and that of Comedy. In fact, in the Euripidean Satyr Play Cyclops, for instance, Silenos sometimes speak like a tragic character, calling the “oarsmen” κώπης ἄνακτας, a familiar expression in Tragedy, and sometimes like a lewd comic hero, alluding unequivocally to his sex with the demostrative pronoun τοῦτο, as we can see in the line: ἵν’ ἔστι τουτί τ’ὀρθὸν ἐξανιστάναι, a typical feature of the Aristophanic Comedy. But Satyr Drema is neither a Tragedy nor a Comedy, neither a Parody of Tragedy nor a special kind of Ancient Comedy. Its effect rests on the mixing up of two unharmonious elements, the tragic and the satyric, that are clearly reflected in its language, sometime noble, elevated, full of rare words and hapax, sometime childish and full of licentiousness and impudence.